Development of cranial muscles in the actinopterygian fish Senegal bichir, Polypterus senegalus Cuvier, 1829. (9th February 2017) - Noda, Masatsugu; Miyake, Tsutomu; Okabe, Masataka
ABSTRACT: Polypterus senegalus Cuvier, 1829 is one of the most basal living actinopterygian fish and a member of the Actinopterygii. We analyzed the spatial and temporal pattern of cranial muscle development of P. senegalus using whole‐mount immunostaining and serial sectioning. We described the detailed structure of the external gill muscles which divided into dorsal and ventral parts after yolk exhaustion. The pattern of the division is similar to that of urodeles. We suggest that, the external gill muscles of P. senegalus are involved in spreading and folding of the external gill stem and the branches. The fibers of the external gill muscles appear postero‐lateral to the auditory capsule. In addition, the facial nerve passes through the external gills. Therefore, the external gill muscles are probably derived from the m. constrictor hyoideus dorsalis. In contrast to previous studies, we described the mm. interhyoideus and hyohyoideus fibers as independent components in the yolk‐sac larvae. The m. hyohyoideus fibers appear lateral to the edge of the ventral portion of the external gill muscles, which are probably derived from the m. constrictor hyoideus dorsalis. These findings suggest that the m. hyohyoidues is derived from the m. constrictor hyoideus dorsalis in P. senegalus . In other actinopterygians, the m. hyohyoideus is derived from the m. constrictor hyoideus ventralis; therefore, the homology of the m. hyohyoidues of P. senegalus and other actinopterygians remains unclear. J. Morphol. 278:450–463, 2017. © 2017 Wiley Periodicals, Inc. Abstract : We describe the m. interhyoideus and m. hyohyoideus each as an independent component in P. senegalus . The m. hyohyoideus develops near the external gill muscles and is probably derived from the m. constrictor hyoideus dorsalis.